2022
DOI: 10.3390/ijms23158263
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate Nanoparticles as a Potential Glioblastoma Therapeutic via Lipid-Mediated Cell Death

Abstract: Polyoxometalate nanoparticles (POMs) are a class of compounds made up of multiple transition metals linked together using oxygen atoms. POMs commonly include group 6 transition metals, with two of the most common forms using molybdenum and tungsten. POMs are suggested to exhibit antimicrobial effects. In this study, we developed two POM preparations to study anti-cancer activity. We found that Mo-POM (NH4)Mo7O24) and W-POM (H3PW12O40) have anti-cancer effects on glioblastoma cells. Both POMs induced morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, a recent report has shown that (NH 4 ) 6 [Mo 7 O 24 ] can induce the peroxidation of phospholipids in the cell membranes of glioblastoma cells, which may be linked to its anti-cancer activity. 254 Therefore, the redox activity of POMs towards lipids should be explored further.…”
Section: Reactivity Of Discrete Metal–oxo Clustersmentioning
confidence: 99%
“…Nevertheless, a recent report has shown that (NH 4 ) 6 [Mo 7 O 24 ] can induce the peroxidation of phospholipids in the cell membranes of glioblastoma cells, which may be linked to its anti-cancer activity. 254 Therefore, the redox activity of POMs towards lipids should be explored further.…”
Section: Reactivity Of Discrete Metal–oxo Clustersmentioning
confidence: 99%